Geschlechter in Un-Ordnung Zur Irritation von Zweigeschlechtlichkeit im Wissenschaftsdiskurs - Hackmann, Nina; Shirchinbal, Dulguun; Wolff, Christina (Verlag Barbara Budrich, 2023)
How do different academic perspectives look at trans, inter and non-binary (TIN) subject positions beyond the bisexual norm and deviancies of heterosexual lifestyles? How are gender diversity and gender role (images) addressed in civil society institutions? The authors discuss highly topical social, legal and everyday practical discourses and demands: The amendment of the Personal Status Act, gender-equal language and a "TINclusive" university.